Chemoresistance in human cancer cell lines: An investigation of active and passive resistance mechanisms and their effect on the dose-response curve of cisplatin. - Nassim, Mark Adel. (University of Ottawa (Canada), 2001)
The shape of the dose-response curve (DRC) has been hypothesized to reflect mechanisms of resistance (Stewart et al. Invest. New Drugs 14:115, 1996). Active resistance (AR) would give rise to a shoulder on a DRC, while passive resistance (PR) would result in a reduced slope or terminal plateau. We obtained DRCs for human small cell lung cancer cells (SBC-3), and for human osteosarcoma cells (Saos-2) exposed to cisplatin (1 hour CP [0.02--40 mug/ml]). We then fit the data to curve models using non-linear regression techniques. We repeated this technique with SBC-3 cells transfected with a gamma-glutamylcysteine synthetase (gamma-GCS) gene, and with Saos-2 cells transfected with a wild-type p53 gene in order to observe their effects on cisplatin resistance. We also repeated these experiments in Saos-2/p53 transfectants whose wild-type p53 production was effectively eliminated, and in SBC-3 and SBC-3/GCS transfectants whose glutathione production was inhibited. Results. Curve modeling of the transfected and parent SBC-3 cell lines suggest that there is a significant difference when the gamma-GCS gene is transfected into this cell line, with changes occurring in the LD50 and the slope after 1 hour exposure (p < 0.001 in both cases). A statistically significant difference is also detected between the transfected and parent Saos-2 cells, where the wild-type p53 gene results in a decrease in the terminal plateau, and a subsequent decrease in PR (p < 0.001). Reversal of the effects of transfection results in an approximate return of the response curve shape to that of the parent cell lines. Conclusions. Our results suggest that drug resistance mechanisms exert an effect on the shape of the dose-response curve.
Keywords: Health Sciences, Pharmacology.